2013
DOI: 10.1016/j.neurobiolaging.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of TREM2 rs75932628 association with Alzheimer's disease in a population-based sample: the Cache County Study

Abstract: Recent studies have identified the R47H variant in TREM2 as an Alzheimer’s disease (AD) risk factor with estimated odds ratio ranging from 2.9–5.1. The Cache County Memory Study is a large, population-based sample designed for the study of memory and aging. We genotyped rs75932628 (R47H) in 2974 samples (427 cases and 2540 controls) from the Cache County study using a custom Taqman Assay. We observed 7 heterozygous cases and 12 heterozygous controls with an odds ratio of 3.5 (95% confidence interval, 1.3–8.8; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 11 publications
3
27
1
Order By: Relevance
“…The finding that TREM2 variants act as strong genetic risk factors for Alzheimer's disease and many other neurodegenerative diseases (Benitez, et al, 2013,Borroni, et al, 2014,Cady, et al, 2014,Giraldo, et al, 2013,Gonzalez Murcia, et al, 2013,R. Guerreiro, et al, 2013a,R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that TREM2 variants act as strong genetic risk factors for Alzheimer's disease and many other neurodegenerative diseases (Benitez, et al, 2013,Borroni, et al, 2014,Cady, et al, 2014,Giraldo, et al, 2013,Gonzalez Murcia, et al, 2013,R. Guerreiro, et al, 2013a,R.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have spurred numerous studies addressing the association between TREM2 and AD and other neurodegenerative diseases. Although negatives have been reported (Jiao, et al, 2014,Miyashita, et al, 2014,Ruiz, et al, 2014,Yu, et al, 2014, the association between TREM2 variants and AD has been confirmed by most studies (Benitez, et al, 2013,Giraldo, et al, 2013,Gonzalez Murcia, et al, 2013,Luis, et al, 2014,Slattery, et al, 2014. Moreover, TREM2 variants were also found to be associated with frontotemporal dementia-like syndrome or FTD (Borroni, et al, 2014,R.…”
Section: Introductionmentioning
confidence: 90%
“…Finally, 14 studies were included in the meta-analysis. 13 studies for rs75932628 [11,12,18,19,21,[27][28][29][30][31][32][33][34], 3 studies for rs104894002 [11,32,35], and 4 studies for rs143332484 [12,28,31,32,35]. The selected study characteristics and allele information are shown in Tables 1 and 2, respectively.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Inconsistent results for associations between rs75932628, rs104894002 (predicted to cause a Q33X substitution), or rs143332484 (predicted to cause a R62H substitution) and AD risk have been constantly reported [11,19,21]. Therefore, we performed a meta-analysis to evaluate the association between the three variants and the risk of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last year, a series of independent studies have reported a strong association of the triggering receptor expressed on myeloid cells 2 ( TREM2 ) gene with Alzheimer’s disease (AD) [17]. For one particular nonsynonymous variant, rs75932628 (encoding R47H), the association reached genome-wide significance [1,2].…”
Section: Introductionmentioning
confidence: 99%